PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PADA PT MOLADIN DIGITAL INDONESIA REGIONAL JAKARTA - Fitriyansyah, Denis; Mualida, Hira (Journal of Research and Publication Innovation, 2023)
This research aims to determine the influence of leadership style and work environment on employee productivity at PT. Moladin Digital Indonesia Regional Jakarta partially and simultaneously. This research is causal associative research with a quantitative approach. The population in this study was 75 employees of PT. Moladin Digital Indonesia Regional Jakarta. The sample used in this research used a nonprobability sampling technique or used a saturated sampling method. The data collection procedure in this research is using a questionnaire using a Likert scale and SPSS 25 programming. The data analysis techniques used are validity and reliability tests, classical assumption tests, simple and multiple linear regression tests, t tests, F tests and coefficient tests correlation and determination. The research results that can be presented are: (1) there is an influence of leadership style on employee productivity (tcount = 11.363 > ttable = 1.665), (2) there is an influence of the work environment on employee productivity (tcount = 7.297 < ttable = 1.665), and (3 ) the influence of leadership style and work environment on employee productivity (Fcount = 75.564 > Ftable = 3.12). So it shows that the leadership style and work environment at PT. Moladin Digital Indonesia partially and simultaneously has a positive and significant effect on employee performance.